A Plural Peninsula: Studies in Honour of Professor Simon Barton
1 online resource (512 pages)
Keywords: A Plural Peninsula embodies and upholds Professor Simon Barton’s influential scholarly legacy, eschewing rigid disciplinary boundaries. Focusing on textual, archaeological, visual and material culture, the sixteen studies in this volume offer new and important insights into the historical, socio-political and cultural dynamics characterising different, yet interconnected areas within Iberia and the Mediterranean. The structural themes of this volume --the creation and manipulation of historical, historiographical and emotional narratives; changes and continuity in patterns of exchange, cross-fertilisation and the recovery of tradition; and the management of conflict, crisis, power and authority-- are also particularly relevant for the postmedieval period, within and beyond Iberia. Contributors are Janna Bianchini, Jerrilynn D. Dodds, Simon R. Doubleday, Ana Echevarría Arsuaga, Maribel Fierro, Antonella Liuzzo Scorpo, Fernando Luis Corral, Therese Martin, Iñaki Martín Viso, Amy G. Remensnyder, Maya Soifer Irish, -Teresa Tinsley, Sonia Vital Fernández, Alun Williams, Teresa Witcombe, and Jamie Wood. See inside the book